2014
DOI: 10.17576/jskm-2014-1202-01
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Polyphenols Consumption and Its Relation with Cognitive and Mental Health in Aging: A Review

Abstract: Literature review suggests that polyphenols in particular fl avonoids, are benefi cial for mental health during aging process. This review examines the effect of consumption of all polyphenols groups on mental health and cognitive status during aging process. The keywords searched were "mental health," "depression," "anxiety," "stress" and "cognitive" combined with "dietary," and "polyphenols Kata kunci yang digunakan adalah "kesihatan mental," "kemurungan," "kebimbangan," "stres" dan "kognitif" disertakan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
1
3
1
Order By: Relevance
“…The evidence is more limited about total stilbenes and cognitive function. In contrast to our results, a previous did not find a significant correlation between stilbenes intake and immediate or delayed recall (31) .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The evidence is more limited about total stilbenes and cognitive function. In contrast to our results, a previous did not find a significant correlation between stilbenes intake and immediate or delayed recall (31) .…”
Section: Discussioncontrasting
confidence: 99%
“…However, as we found in our study, Rosli et al showed a positive correlation between lignan intake and punctuation in immediate memory measured by the Rey auditory verbal learning test (RAVLT) (31) . The evidence is more limited about total stilbenes and cognitive function.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Fruits and vegetables are the source of phytochemicals and major contributors of dietary polyphenols that provide protective mechanism such as antioxidant and anti-inflammatory for human (Hervert-Hernández et al 2011;Slavin & Lloyd 2012). Polyphenol consumption also shows beneficial effects on cognitive and mental health status especially among elderly (Rosli et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Ministry of Health Malaysia 2010) as ulam tends to increase the serum of Vitamin C, E, folic acid, β-carotene and lycopene. It has also been reported to be rich in polyphenols (Su & Arab 2006) that may be beneficial in improving cognitive status (Rosli et al 2014). Medicinal plants such as herbs and ulam are therapeutic agents which have been used in many cultures but studies regarding the development of ulam as fortified food products are still limited.…”
Section: Introductionmentioning
confidence: 99%